Media Pembelajaran Berbasis Multimedia Bagi Guru Madrasah Tsanawiyah (MTs) Nuril Huda dan Madrasah Aliyah (MA) Nuril Huda Tarub - Grobogan - Ahmad Ashifuddin Aqham; Indra Ava Dianta; Moh Muthohir (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
The purpose of this community service is to provide counseling and training in making multimedia-based learning media as a good online digital-based learning tool, understand the manufacture of multimedia-based learning media, be able to apply the knowledge gained and be involved in managing multimedia-based learning for MTs teachers and MA Nuril Huda Grobokan.